Argentina’s Energy Governance in the 21st Century: Unraveling its Central Issues - Ceppi, Natalia (2022)
For the Social Sciences in general, the notion of governance represents a polysemic and controversial category whose content depends on the used conceptual approach. However, in the field of natural resources, specifically energy, governance is understood as an analytical tool that, by focusing on the decision-making process, makes it possible to examine, through cases, the exercise of State authority, the rules of the game and public-private interactions in the energy sector. This paper analyzes the energy governance process of Argentina during Cristina Fernández (2007-2015) and Mauricio Macri (2015-2019) administrations. Due to their political-ideological differences, ruptures and continuities are traced with a view to addressing the political-economic dimension of energy management as a topic of the public agenda, whose implications are presented both domestically and in foreign policy decisions.